Structural characteristics and problems of dairy farms in balıkesir province - Burak Mat; Yavuz Cevger (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to reveal the structural characteristics and production problems of dairy farms in Balıkesir province. Materials and Methods: The material of the study was obtained from the establishments located in Balıkesir provinces and districts and which are members of the Balıkesir Cattle Breeders Association, using the questionnaire. In determining the sample, the stratified sampling method was used and 135 enterprises were calculated. The variables are mean ± standard deviation and Median (Maximum-Minimum) percentage and frequency values are used. While performing data analysis, Kruskal Wallis and Bonferroni-Dunn tests were used for comparing three or more groups. Results: It was determined that 49.6% of dairy cattle enterprise owners were high school graduates and 63% did not participate in any training related to dairy cattle breeding. While the technology usage rate is 10.3% in small-scale enterprises, this rate has reached 100% in large-scale enterprises. It has been determined that dairy farms produce an average of 68% of the roughage that they use as input. According to the data obtained from the enterprises, an average of 5.51 tons of milk was obtained in 2017 and 5.40 tons of milk in 2018 from one cow in a lactation period. Conclusion: In the province of Balıkesir, economic transformation and development has been experienced in favor of the tourism and industry sectors in recent years. This situation decreases pasture areas and forage crop production and therefore livestock sector is negatively affected at provincial level. It was determined that some yield parameters of dairy cattle farming within the scope of the research deviated from the desired standard values. With the measures to be taken and the training studies to be carried out in these enterprises, these efficiency parameters will be brought to the desired values and will enable the enterprises to increase their profitability and efficiency. The realization of this increase in dairy cattle in Turkey with long-term to ensure self-sufficiency in the sector and will contribute significantly to minimizing the import of livestock.